2016
DOI: 10.18632/oncotarget.9700
|View full text |Cite
|
Sign up to set email alerts
|

Direct contact with perivascular tumor cells enhances integrin αvβ3 signaling and migration of endothelial cells

Abstract: The secretion of soluble pro-angiogenic factors by tumor cells and stromal cells in the perivascular niche promotes the aggressive angiogenesis that is typical of glioblastoma (GBM). Here, we show that angiogenesis also can be promoted by a direct interaction between brain tumor cells, including tumor cells with cancer stem-like properties (CSCs), and endothelial cells (ECs). As shown in vitro, this direct interaction is mediated by binding of integrin αvβ3 expressed on ECs to the RGD-peptide in L1CAM expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…In addition, complex molecular signaling and crosstalk between glioma cells and the cells of the NVU also dictate tumor survival and progression (71)(72)(73)(74). These cell-cell interactions promote tumorigenic processes and disrupt normal NVU functions.…”
Section: Neoplastic Diseasementioning
confidence: 99%
“…In addition, complex molecular signaling and crosstalk between glioma cells and the cells of the NVU also dictate tumor survival and progression (71)(72)(73)(74). These cell-cell interactions promote tumorigenic processes and disrupt normal NVU functions.…”
Section: Neoplastic Diseasementioning
confidence: 99%
“…Regarding PI3K/Akt, a recent study associates this pathway with Plexin-B1/Rho/αvβ3 and Serine/arginine Protein Kinase-1 [ 79 ]. Moreover, migration can be improved by αvβ3 interaction with pleiotrophin (a secreted heparin-binding cytokine) on GB cells and EC [ 80 ] and with the cell adhesion molecule L1CAM on GIC [ 81 ]. Besides αvβ3/αvβ5, β1 is also involved in GB angiogenesis [ 76 ].…”
Section: Roles Of Integrins In Glioblastomamentioning
confidence: 99%
“…The expression of L1CAM by various types of cancer cells is utilized to engage αVβ3 on endothelial cells. It has been demonstrated that L1CAM expression in glioma tumor cells serves to promote the motility of both cancer cells [ 31 ] and endothelial cells [ 32 ], thus having important implications for both metastasis and angiogenesis, respectively. Other non-ECM integrin ligands have been implicated in tumor cell migration.…”
Section: Integrin-mediated Cell-cell Interactionsmentioning
confidence: 99%